Analysis, Reconstruction and Establishment Tourist Destination in Toba Samosir, North Sumatera, Indonesia - Simanjuntak, Menara; Sarjono, Haryadi (Bina Nusantara University, 2012)
This study aimed to provide inputs for local government of Toba Samosir (Tobasa) in preparing strategic development plan of tourist destinations in District Tobasa. This study is a qualitative approach through in-depth interviews and feedback from forum discussion groups with participants representing community leaders, indigenous peoples, governments and travel business. Total participants are 15 people collected on June 1, 2012 at Balige government office. Discussion forums formulated nine locations of tourist destination spread in Toba Samosir. As result this research, we formulated four strategic plans with tactical plans; (1) specifying and establish the location of tourist destinations in the District Tobasa; (2) submitting plans to the government budget or through the budget of Tobasa district in five years starting in 2014 to follow; (3) conducting government financing for infrastructure development and tourism industry participation; (4) doing tourism and cultural promotion. We found limitations for the plan. Some of them were: the low budget provided by the District government so that we expected supports from domestic investors to accelerate tourism development in the area. Most activities were proposed under the action plan of both Tobasa District government and North Sumatra Government.